Efeito da inundação sobre a estrutura da comunidade terrestre de Coleoptera (Arthropoda, insecta) : estudo comparativo entre áreas inundáveis e não inundáveis no Pantanal de Poconé - Mato Grosso - Carneiro, Andrea Correia (2012)
The Pantanal comprises a mosaic of landscapes strongly influenced by seasonal mono mode flood pulse, which imposes a spatial and temporal dynamics in the composition of the arthropod community sites, especially Earth community. To better understand the functioning of this complex ecosystem is essential to study the effects of these dynamics on invertebrate communities in different landscape places. Based on this premise this study aimed to evaluate the effect of flooding on the terrestrial community structure of Coleoptera, through a comparative study between flooding areas and not flooding areas in the flat ground of Pantanal in Poconé- MT. Samples were collected during from the drought /2010 and flood season/2011 of this region into three areas (A1, A2 and A3) selected in the distance between the rivers Bento Gomes and Cuiabá. In each area were delimited three points (N = 3) considered replicas, where were demarcated two quadrants of 10x10m, corresponding to treatments in flooded and not flooded environments, totaling 18 quarters. In these quadrants were distributed nine pitfall traps without bait, and collected two m2 litter and topsoil to capture Coleoptera with extractor mini-Winkler. The Coleoptera community was represented by 4260 adult sampled belonging to 36 families, 113 genders and 505 species/morphospecies. The largest number of individuals was obtained for the families Staphylinidae (848 ind., 19.9%), Nitidulidae (729 ind., 17.1%), Scarabaeidae (472 ind.; 11.1%), Curculionidae (470 ind ., 11.0%), Corylophidae (407 ind., 9.6%) and Carabidae (311 ind., 7.3%). The structure of the Earth community ordinate by non-metric multidimensional scaling (NMDS) showed a tendency of separation between drought and flood, however, did not indicate a separation between the physiognomies flooded and not flooded. There was temporal and spatial variation in the structure and composition of the community, since the period had more drought/2010 families (28 families) and individuals (2,007 ind.) Compared to flood/2011 (20 families, 761 ind.), and only 16.6% of the species/ morphospecies collected were common to both periods. The environments do not flood were more abundant (2,007 ind.; 57.4%) than the flood (1,492 ind., 42.6%) and 37.7% of species were common to these two environments. The two methods created different information about the composition and community structure of terrestrial Coleoptera therefore among the 505 species collected in this study, only 49.9% were collected using pitfall traps, and 29.0% using only the extractor mini-Winkler. The ordering by NMDS showed that the variation of the data structure (abundance) of the community was separated according to the used methods. Therefore, the two methods were complementary and contributed to a broader sampling of the community. These results suggest a change in the structure of the species composition of the community of Coleoptera influenced both by extreme hydrological variability of sampling periods, as the areas sampled and conditions of flooded or not flooded environments that represent formations phytophysiognomical suffering direct and indirect effect of the floods. But it will need additional studies to evaluate other variables that may influence this distribution in the Pantanal.